A technique for reducing the PMEPR of MC-CDMA signals - Silva, Paulo (2004)
In this paper we consider the use of MCCDMA (Multi-Carrier Code Division Multiple Access) schemes with a frequency-domain orthogonal spreading. The transmitter structure is especially modified for reducing the envelope fluctuations of the transmitted signals. An analytical approach for the performance evaluation is also included which relies on the Gaussian characteristics of MC signals with a high number of suhcarriers. A set of performance results is presented. Our performance results show that the proposed transmitter structure is adequate for power-efficient MC-CDMA transmission since we can reduce the envelope fluctuations of the transmitted signals, while keeping essentially the same spectral efficiency of the conventional MC-CDMA transmission.